2017
DOI: 10.1111/aos.13338
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between optic disc drusen and optic disc oedema using fundus photography

Abstract: In the patients with blurred disc margin, the presence of a halo strongly suggested underlying ODD rather than ODE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(65 reference statements)
2
4
0
1
Order By: Relevance
“…On one hand, the funduscopic distortion induced by ODD was measured as ‘Relative Disc Index.’ Relative Disc Index was calculated as the proportion between the longest diameter of the funduscopic disc margin and the fovea-to-disc diameter ( Fig 1 , a / b ). Unlike type 2 ODD, the disc margin of type 1 ODD was not clearly discernible, due to the halo, as previously reported [ 15 ]. Halo was defined as a blurring of the optic disc margin on the fundus photographs [ 15 ].…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…On one hand, the funduscopic distortion induced by ODD was measured as ‘Relative Disc Index.’ Relative Disc Index was calculated as the proportion between the longest diameter of the funduscopic disc margin and the fovea-to-disc diameter ( Fig 1 , a / b ). Unlike type 2 ODD, the disc margin of type 1 ODD was not clearly discernible, due to the halo, as previously reported [ 15 ]. Halo was defined as a blurring of the optic disc margin on the fundus photographs [ 15 ].…”
Section: Methodssupporting
confidence: 75%
“…Unlike type 2 ODD, the disc margin of type 1 ODD was not clearly discernible, due to the halo, as previously reported [ 15 ]. Halo was defined as a blurring of the optic disc margin on the fundus photographs [ 15 ]. In these cases, we measured the longest diameter of the halo ( Fig 1A ), since we wanted to measure the distortion induced by ODD, and not the actual disc size on the funduscopic plane.…”
Section: Methodssupporting
confidence: 75%
“…Lee et al beschrieben 2017 ein Zeichen, das die Diagnose der Drusenpapille erleichtern könnte [5]. Es handelt sich um ein C-förmiges Halo am nasalen Papillenrand, das sich nur bei Drusenpapil-…”
Section: Funduskopie Des Patientenunclassified
“…Using EDI OCT, a new feature of the swollen optic nerve has been identified and termed peripapillary hyperreflective ovoid mass-like structure (PHOMS). Although the term PHOMS was codified as a feature seen in association with ONHD by the Optic Disc Drusen Studies Consortium [1,5,[7][8][9], subsequent studies have shown that PHOMS may be a feature of papilledema, papillitis, myopia, and anomalous optic nerves [10][11][12].…”
Section: Introductionmentioning
confidence: 99%